(untitled) (Indian Journal of Animal Production and Management, 2024)
The present experiment was conducted to study the effect of sea buckthorn leaf meal (SBTLM) supplementation on hen house and hen day egg production in ninety coloured Chabro adult breeder hens and 18 viable cocks in 1:5 sex ratio were randomly distributed into three dietary treatment groups: Control, standard basal breeder diet (BIS, 2007); basal+0.5% and basal+1.0% SBTLM. The average egg production during 9th week onward till the entire period of experimentation were significantly higher (p<0.01) in both SBTLM supplemented groups (basal diet+0.5% SBTLM and basal diet+1.0% SBTLM) as compared to control group (basal diet). However, it was also observed that from 3rd week to 5th week of experimentation, the weekly hen house egg production were significantly higher (p<0.05) in both the SBTLM supplemented groups than the control group. The overall egg production up to the 12th week of experimentation were significantly higher (p<0.01) in both the SBTLM supplemented groups as compared to control group. During the experimental study period, there was no mortality in any treatment group. Hence, the hen day egg production per week and phase wise hen day egg production per week was equal to the hen house egg production per week egg production.